Bioinspired Divergent Oxidative Cyclization from Strictosidine and Vincoside Derivatives: Second‐Generation Total Synthesis of (−)‐Cymoside and Access to an Original Hexacyclic‐Fused Furo[3, 2‐b]indoline. Issue 71 (18th November 2020) - Dou, Yingchao; Kouklovsky, Cyrille; Vincent, Guillaume
Abstract: The second‐generation synthesis of (−)‐cymoside as well as the formation of a new hexacyclic‐fused furo[3, 2‐ b ]indoline framework is reported. After a Pictet–Spengler condensation between secologanin tetraacetate and tryptamine, the course of the cyclization of the 7‐hydroxyindolenine intermediate, generated by oxidation with an oxaziridine, depended on the stereochemistry of the 3‐position. The 3 ‐ ( S )‐strictosidine stereochemistry delivered efficiently the scaffold of cymoside via intramolecular coupling with the C16–C17 enol ether, while the 3 ‐ ( R )‐vincoside stereochemistry directed towards the reaction with the C18–C19 terminal alkene and the formation of the unexpected caged compound. Abstract : The next generation : The oxidative cyclization of an enantiopure strictosidine derivative leads to the total synthesis of (−)‐cymoside, while the corresponding 3‐epimeric vincoside derivative delivers a new hexacyclic‐fused furo[3, 2‐ b ]indoline framework.